Dynamic load balancing algorithm based on queuing theory comprehensive index evaluation - Wenbo WANG; Qingwei YE; Yu ZHOU; Zhihua LU (Dianxin kexue, 2018)
Internet communication,computer cluster and cloud environment have complex and dynamic characteristics,which can cause load imbalance easily,reduce the service efficiency and increase the energy consumption.Therefore,the load balancing technology becomes the focus of research.The existing load balancing strategy uses the occupancy of CPU,memories,processes to estimate the current load of each server.But it is hard to guarantee its accuracy.Aiming at this problem,a dynamic load balancing algorithm based on queuing theory comprehensive index evaluation was proposed.Firstly,queuing theory model was introduced to estimate the real-time load of each server,and then the tasks of input queue was distributed to each server separately according to the load comprehensive index of each server.Experimental results show that this method can balance the load of each server effectively and reduce the average waiting time of the task requests,which is of great application value.